The Role of Quality Management System in Risk Management in Organization - Zapłata , Sławomir (Studia Oeconomica Posnaniensia, 2016)
"Risk-based thinking" within quality management systems, according to ISO 9001:2015 requirements, represents the main idea of this paper. Theoretical and practical issues in that area are presented. The topic of this paper is subordinated to issues from the general to the details. After an introduction to quality management systems, the author describes a conception of risk management in organization and business continuity management. This system concerns quality and risk, which implicates activities in the area of quality management system. Next, ideas of risk-based thinking application within quality management system are presented. ISO 9001:2015 requirements, which affect risk, are also shown. In the final part of paper, the author presents the practical aspects of risk-based thinking in quality management area.